Ocorrência de Felis catus gammaherpesvirus 1 (FcaGHV1) e coinfecções com patógenos virais felinos em gatos domésticos no Brasil - Kurissio, Jacqueline Kazue [UNESP]; Rodrigues, Marianna Vaz [UNESP]; Taniwaki, Sueli Akemi; Zanutto, Marcelo de Souza; Filoni, Claudia [UNESP]; Galdino, Maicon Vinícius [UNESP]; Araújo Júnior, João Pessoa [UNESP] (FapUNIFESP (SciELO), 2018)
Felis catus gammaherpesvirus 1 (FcaGHV1) may causes an asymptomatic infection that result in an efficient transmission and subsequently dissemination of the virus in feline population. This study used molecular detection by qPCR (quantitative PCR) based on DNA polymerase gene fragment amplification to evaluate the occurrence of FcaGHV1 and its correlation with other feline viral pathogens, such as Carnivore protoparvovirus 1 (CPPV-1), Felid alphaherpesvirus 1 (FeHV-1), and feline retroviruses such as feline immunodeficiency virus (FIV) and feline leukemia virus (FeLV). Of the 182 blood samples evaluated 23.6% (43/182) were positives for FcaGHV1. Approximately 37.9% (33/87) of the samples that tested positive for retrovirus were also were positive for FcaGHV1 infection (P<0.0001). Among FIVinfected samples, 49% (24/49) were positive for FcaGHV1 (P<0.0001). FcaGHV1 infection was not associated with FeLV (P>0.66) or CPPV- 1 (P>0.46) coinfection. All samples were negative for FeHV-1. Male felines were significantly associated to FcaGHV1 (P<0.0001) and their risk of infection with FcaGHV1 was about of 7.74 times greater compared to females. Kittens (≤ 1year) were the least affected by FcaGHV1 infection, being verified a rate of 7.7% (4/52). Therefore, male cats over one year old and infected with FIV were considerably more likely to be infected with FcaGHV1. To our knowledge, this is the first study to report the occurrence and molecular detection of FcaGHV1 infection in domestic cats in Brazil and in South America.
Felis catus gammaherpesvirus 1 (FcaGHV1) and coinfections with feline viral pathogens in domestic cats in Brazil
Keywords: Diagnosis; Feline pathogen; Gammaherpesvirus; Herpesvirus; Infectious diseases